Marriage Prestations, Gift Making, and Identity in Urban East Timor. Issue 1 (6th February 2018) - Silva, Kelly
Abstract : This article addresses the current praxis and controversies framing marriage prestations in urban East Timor. Drawing on data related to practices, narratives, and social location of agents who stand for and against barlake (the local name for a part or the whole of marriage prestations), it suggests how the association of marriage transactions with different regimes of exchange – namely, gift and commodity – is a means for producing prestige and social distinction between ema Dili and ema foho . The lack of consensus about a single meaning for barlake allows everyone to reproduce their commitments with local and global expectations of modernity. Such phenomena result from ascribing marriage prestations to the gift regime of exchange, regardless of the number or the kind of gift functions implied in them. The controversies surrounding barlake entail a moral narrative of modernity structured by anxieties related to: (1) fixing ontological boundaries between people and things; (2) the alliance effects people search for when carrying out their marriage; (3) the social history and politics of custom associated with Dili as a place of civilized/assimilated people, and, finally; (4) people's historical period of migration to the city.